Rasio Keuangan, Financial Distress Dalam Prediksi Kebangkrutan Perusahaan Manufaktur - Firda Rismadhani; Ana Kadarningsih (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Financial distress is a financial condition of a company that is in a state of crisis. The purpose of this study is to find out the effect of liquidity, leverage, operating capacity, profitability, and firm growth on financial distress. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange in 2017-2018 with the sampling technique using porposive sampling or criteria. Based on the technique, obtained sample of 112 companies. The results of this study indicate that liquidity and profitability has a significant effect on the financial distress of manufacturing companies listed on the Indonesian stock exchange. Meanwhile, leverage, operating capacity, and firm growth have no effect on the financial distress of manufacturing companies listed on the Indonesian Stock Exchange.